Confirmation of NKX3-1 Expression in EWSR1-NFATC2 Sarcoma and Mesenchymal Chondrosarcoma Using Monoclonal Antibody Immunohistochemistry, RT-PCR, and RNA In Situ Hybridization. (April 2021) - Yoshida, Akihiko; Hashimoto, Taiki; Ryo, Eijitsu; Yoshida, Ken-ichi; Motoi, Toru; Yatabe, Yasushi; Mori, Taisuke
Abstract : Supplemental Digital Content is available in the text.